Alleviation of Oxidative Damage Induced by CaCl2 Priming Is Related to Osmotic and Ion Stress Reduction Rather Than Enhanced Antioxidant Capacity During Germination Under Salt Stress in Sorghum - Chen, Xiaofei; Zhang, Ruidong; Li, Bang; Cui, Tong; Liu, Chang; Liu, Chunjuan; Chen, Bingru; Zhou, Yufei (Frontiers in Plant Science, 2022)
Seed germination is the sensitive period to salt stress. Calcium chloride (CaCl2) has been proved as an effective priming agent which can promote the sorghum germination under salt stress. However, there are few reports on CaCl2 priming to improve the salt tolerance during seed germination. The present study investigated the effects of CaCl2 priming on sorghum germination, antioxidant metabolism, osmotic regulation and ion balance under salt stress (150mM NaCl). The results revealed that the salt stress inhibited the elongation of mesocotyl and root and reduced the germination rate of sorghum. While CaCl2 priming significantly promoted the elongation of mesocotyl and root, and increased the germination rate of sorghum under salt stress. CaCl2 priming notably increased the content of osmotic substances in mesocotyl and root of sorghum under salt stress, and increased the relative water content in these tissues. CaCl2 priming decreased Na+ content and increased K+, Ca2+ contents and the K+/ Na+ in mesocotyl and root, such effects might be induced by up-regulating the expression of NHX2, NHX4, SOS1, AKT1, AKT2, HKT1, HAK1, and KUP. CaCl2 priming reduced the antioxidant enzymes activities and related gene expression compared with untreated sorghum seeds under salt stress. In short, CaCl2 priming improved sorghum germination by enhancing osmotic regulation and ion balance instead of antioxidant enzyme activity. However, the molecular mechanisms of Ca2+ signaling induced by CaCl2 priming in association with the enhanced germination in primed sorghum seeds under salt stress need to be addressed in future studies.